Production of functional graphene by kitchen mixer: mechanism and metric development for in situ measurement of sheet size - Zulhelmi, Ismail; Abdullah, Abu Hannifa; Zainal Abidin, Anis Sakinah; Kamal, Yusoh (Springer Berlin Heidelberg, 2017)
It has been reported that the production of defect free graphene is possible by the application of a kitchen mixer. Yet, we note that the natural-surfactant role in the exfoliation mechanism by a kitchen mixer has rarely been discussed. To investigate the possibility of graphene exfoliation in a bio-surfactant medium, we have produced graphene from the co-mixing of graphite and gum Arabic. Through the modelling of bulky graphite as a single composite disc, we have shown that the exfoliation of graphite crystal may be possible through rotational motion of graphite surface. In this paper, we also have developed two simple metric systems that were designed from the application of UV spectroscopy for in situ measurement of graphene sheet size after exfoliation step.